2004
DOI: 10.1126/science.1095069
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Atomic Doping of a Single C 60 Molecule

Abstract: We report a method for controllably attaching an arbitrary number of charge dopant atoms directly to a single, isolated molecule. Charge-donating K atoms adsorbed on a silver surface were reversibly attached to a C60 molecule by moving it over K atoms with a scanning tunneling microscope tip. Spectroscopic measurements reveal that each attached K atom donates a constant amount of charge (approximately 0.6 electron charge) to the C60 host, thereby enabling its molecular electronic structure to be precisely and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 19 publications
3
57
0
Order By: Relevance
“…Shifts of molecular states induced by metal-molecule contact have been reported in different systems [4][5][6][7][8][9][10][11][12][13][14], but cumulative shifts by multiple contacts have rarely been reported. To our knowledge, the only example is that in K x C 60 complexes the C 60 states are down shifted cumulatively due to stepwise charge transfer (each attached K atom donates $0:6e to the C 60 host) [10]. DFT calculations conclude that there is no significant charge transfer between the TPyB molecule and the coordinated Cu atoms (less than 0.1 electrons from Bader charge analysis), thus excluding that the observed energy level shifts are caused by charging effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shifts of molecular states induced by metal-molecule contact have been reported in different systems [4][5][6][7][8][9][10][11][12][13][14], but cumulative shifts by multiple contacts have rarely been reported. To our knowledge, the only example is that in K x C 60 complexes the C 60 states are down shifted cumulatively due to stepwise charge transfer (each attached K atom donates $0:6e to the C 60 host) [10]. DFT calculations conclude that there is no significant charge transfer between the TPyB molecule and the coordinated Cu atoms (less than 0.1 electrons from Bader charge analysis), thus excluding that the observed energy level shifts are caused by charging effects.…”
mentioning
confidence: 99%
“…Scanning tunneling microscopy and spectroscopy (STM-STS) have been used to address this challenging problem owing to their capability of resolving geometric details of molecule-metal contacts and simultaneously measuring the single-molecule electronic properties. These studies revealed in great detail that the molecular frontier orbitals are modulated when the molecules are coupled to metal atoms or a metal substrate [4][5][6][7][8][9][10][11][12][13][14]. So far, most of these studies focused on molecules coupled to one or at most two metal contacts.…”
mentioning
confidence: 99%
“…Photoemission spectra obtained from an increasingly K-doped monolayer of C 60 on Ag(111) shows a triply degenerate LUMO progressively filling with electrons, but no splitting [17]. In contrast, a study [30] using STM techniques to sequentially K-dope an individual C 60 molecule on a Ag(001) surface showed a clear splitting in the dI/ dV spectrum of the undoped C 60 , as shown in Fig. 7.…”
Section: Monolayersmentioning
confidence: 95%
“…Of particular merit is the work of Crommie and co-workers who, in a series of papers [30,5,38,39], have recorded some very intriguing images and spectra of a series of doped C 60 molecules. In one experiment [on Ag(111)], these workers were able to use the STM tip to progressively attach/detach potassium atoms to individual C 60 molecules and subsequently record the scanning tunnelling spectroscopy data shown in Fig.…”
Section: Stm Imaging Of Fullerenes: An Overviewmentioning
confidence: 99%
“…Fullerene's large electron affinity is known to yield to electron transfer into C 60 when adsorbed on metallic substrates. The actual number of doped electrons depends on the substrate[4], but may also be controlled by attaching alkali atoms to the molecule [5]. In this case a variety of conductance behavior has been reported depending on the number of K-atoms attached to C 60 [5], ranging from Kondo-like resonances to Fano-like anti-resonances.…”
mentioning
confidence: 99%